The Effect of Bank Syariah Indonesia Merger on Financing in Indonesia - Achsani, Muhammad Nur Faaiz Fathah; Irfany, Mohammad Iqbal (Ekonomi Islam Indonesia, 2025)
This study aims to examine the impact of the merger of three state-owned Islamic banks on financing in Indonesia’s Islamic banking sector, while also analyzing the role of macroeconomic and bank-specific factors. The study employs time-series data and applies the Auto-Regressive Distributed Lag (ARDL) bounds testing approach to analyze short- and long-term relationships between financing and various macroeconomic and bank-specific variables. The results show that in the short run, the merger did not have an immediate effect on financing, with key variables such as asset size, non-performing financing (NPF), exchange rates, and the unemployment rate significantly influencing financing. In the long run, asset size and NPF positively and negatively impacted financing, respectively, while the exchange rate negatively influenced financing. The merger itself showed no significant long- term effect, likely due to the bank focusing on internal consolidation rather than expanding financing or market share. This study provides insights into the immediate and long-term impacts of bank mergers in the context of Islamic banking, emphasizing the role of macroeconomic factors and internal consolidation processes. The findings offer valuable guidance for policymakers, regulators, banks, and stakeholders in the Islamic banking industry.